Synthesis Of Elements And Increased Radionuclide Activity Induced By Supersonic Spiral Jet - Kholmurad Khasanov; Elena Urusova; Rashid Eshburiev (Zien Journals, 2025)
Intranuclear leakage of liquid protons was experimentally observed during the deceleration phase of the spiral-waved jet emitted from Kholmurad Khasanov's dynamic emitter. The gas stream from the nozzle forms supersonic spiral-type jets with spatially modulated extreme density, enhanced by shockwave structures. In these jets, phenomena such as over-compression and over-acceleration occur, creating a high-density energy field as the internal energy of the gas or liquid decreases. The resulting instability within the jet leads to explosions accompanied by intense ultraviolet light flares. These conditions are hypothesized to promote the synthesis of new elements and increase radionuclide activity, as verified by gamma-spectrometric analysis. In the experiments, elements such as carbon, calcium, silicon, and aluminum—previously absent in the original samples—were detected on solid surfaces after exposure to the jet
Keywords: Dynamic emitter; Over-compression; Ultraviolet irradiation explosion